Cybersecurity Virtual Laboratory for distance learning - Yeremenko, O.; Yevdokymenko, M.; Kuzminykh, I.; Kruhlova, A. (ACM, 2020)
In the conditions of distance learning of university students, there is a problem of practical and laboratory work organization. This is especially true of technical universities, where training in ordinary conditions is carried out on real equipment and using specialized software. In this regard, there is an urgent need to create a virtual laboratory, as an effective platform for distance learning students.
Keywords: Cybersecurity; Virtual laboratory; Education; Distance learning